2011
DOI: 10.3892/mmr.2011.619
|View full text |Cite
|
Sign up to set email alerts
|

Patients with progressive pseudorheumatoid dysplasia: From clinical diagnosis to molecular studies

Abstract: Abstract. Progressive pseudorheumatoid dysplasia (PPD) is a rare inherited autosomal recessive disease for which no prevalent data have been reported in China. We aimed to identify PPD based on clinical manifestations and imaging analysis of the bony skeleton and then to investigate gene mutations of Wnt1-inducible signaling pathway protein 3 (WISP3) in Chinese patients with PPD. Seven patients (aged 9-49 years) from six unrelated Chinese families all presented with a waddling gait, progressive swelling and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
2
28
1
Order By: Relevance
“…We found that the proband carried a frameshift mutation (c.670dupA) and a nonsense mutation (c.756C > A, p.Cys252*) in exon 4 of WISP3 (Fig. 2a, b), which have been reported previously [7, 8]. Furthermore, the frameshift mutation (c.670dupA) was found in the paternal allele (Fig.…”
Section: Case Presentationsupporting
confidence: 85%
See 3 more Smart Citations
“…We found that the proband carried a frameshift mutation (c.670dupA) and a nonsense mutation (c.756C > A, p.Cys252*) in exon 4 of WISP3 (Fig. 2a, b), which have been reported previously [7, 8]. Furthermore, the frameshift mutation (c.670dupA) was found in the paternal allele (Fig.…”
Section: Case Presentationsupporting
confidence: 85%
“…Subsequently, a total of 18 WISP3 mutations located in exons 2 to 5 have been described in China (Table 1) [2, 7, 8, 1115]. They include five different mutations (two frameshift mutations and one nonsense mutation) located in exons 2 and 3 (two missense mutations), respectively, as well as five mutations in exon 5 (three frameshift mutations, one nonsense mutation and one missense mutation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WISP3 gene spans over 5 exons and encodes several functional domains each corresponding to one of the exons. Exon 1 encodes a peptide sequence that plays role in Wisp secretion (7,(10)(11)(12); exon 2 codes for insulin-like growth factor binding proteins (IGFBPs) that contains twelve cysteine residues (7,10,12-15); exon 3 encodes a cysteine rich, von Willebrand factor type C repeat domain (10,11,13,15); exon 4 contains information for a thrombospondin type 1 domain biosynthesis (with six cysteine residues) that may bind to sulfated glycosaminoglycan's either at cell surfaces or in extracellular matrix (11,12,(15)(16)(17)(18); and exon 5 that encodes a cysteine knot domain comprised of ten cysteine residues possibly involved in dimerization and receptor binding (10)(11)(12)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24). Until now, a number of mutations and polymorphisms were found throughout the WISP3 sequence with geographically localized origin ( Table 2).…”
Section: Discussionmentioning
confidence: 99%